Pengaruh speed training terhadap performa fisik pemain futsal remaja - Apriantono, Tommy; Juniarsyah, Agung Dwi; Adnyana, I Ketut; Hasan, Muhamad Fahmi; Resmana, Dadan (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
High intensity and good acceleration speed are distinct advantages in a futsal team, thus the purpose of this study is to determine the effect of speed training on the physical performance of futsal players in West Java. The method used in this research is experimental, with a pretest–posttest one group design approach. A purposive sampling technique with inclusion criteria was used in selecting subjects. The total subjects were 30 male futsal players with an average (age of 18.18 ± 2.11 years, height of 168.20 ± 5.32 cm, weight of 60.49 ± 4.23 kg, and fat of 10.19 ± 1.65 %). Data were analyzed using the SPSS version 22 application with a significance level of p <0.05. The results showed that speed training carried out for 10 weeks significantly impacted aerobic Capacity (p=0.005) and agility (p=0.008). While for the vertical jump and 20-meter sprint, there was an increase, but not significant. Thus the findings in this study can be used as a recommendation for coaches and athletes to train in the basic components of speed to help their physical performance properly.